The secrets she keeps ebook A novel. - Robotham, Michael (2017)
"Two terrific female characters, both with secrets. Add Michael Robotham's clean prose and whipcrack pacing. The result? A book you won't be able to put down, although you may occasionally want to hide your eyes." —Stephen King "A premium delivery." — People Meghan doesn't know Agatha, but Agatha knows Meghan. And the one thing Agatha looks forward to each day is catching a glimpse of her, the effortlessly chic customer at the grocery store where she works stocking shelves. Meghan has it all: two adorable children, a handsome and successful husband, a happy marriage, a beautiful house, and a popular parenting blog that Agatha reads with devotion each night as she waits for her absent boyfriend, the father of the baby growing inside her, to return her calls. Yet if Agatha could look beyond the gloss and trappings of Meghan's "perfect life," she'd see the flaws and doubts. Meghan has her secrets too, especially one that she dare not ever tell. Soon the lives of these two women will collide in the most spellbinding and intimate of ways, until their secrets are exposed by one shocking act that cannot be undone. From internationally bestselling author Michael Robotham, The Secrets She Keeps is a dark, exquisite, and twisted page-turner so full of surprises, you'll find it impossible to put down.